Securing networks in the Internet of Things era. (April 2015) - Liu, Cricket
Abstract : We all know that the Internet of Things (IoT) is coming, and its sheer scale alone is almost mind-boggling: Gartner reckons that the number of connected devices will hit 26 billion by 2020, almost 30 times the tally of devices connected to the IoT in 2009. 1 This estimate doesn't even include connected PCs, tablets and smartphones. Organisations' networks are already being invaded by a dizzying variety of Internet-connected 'things', often purchased and deployed by departments without consulting the IT people who will be responsible for managing and securing them. IT departments need to respond to this threat now, warns Cricket Liu of Infoblox. At the very least, they need to have a discussion with the rest of the business about what devices can and can't be introduced into the corporate environment. And there are some highly effective technical solutions – such as a move to IPv6 – that can help with the problem.